2021
DOI: 10.3390/su13116279
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Small-Scale Fishers’ Individual Perceived Wellbeing Satisfaction in Southern Benin

Abstract: In southern Benin, the rapid growth of demographics and the need for fishery products have forced public managers to adopt various management measures in the face of anti-ecological methods used by fishers; however, these strategies are often formulated independent from the context. These measures have not remained without consequence on the daily lives of fishers. This paper examines factors influencing fishers’ individual perceived wellbeing satisfaction using the social-ecological system framework. Data on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…The two bodies of water maintain a permanent link through the three-kilometer-long Totchè channel (Figure 1). This area was selected for the study following previous works [18,19] which demonstrated the existence of the problem of property rights on the water in these two towns.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…The two bodies of water maintain a permanent link through the three-kilometer-long Totchè channel (Figure 1). This area was selected for the study following previous works [18,19] which demonstrated the existence of the problem of property rights on the water in these two towns.…”
Section: Study Areamentioning
confidence: 99%
“…Moreover, in these territories, access, extraction, exclusion, and alienation of property rights are inherited from endogenous legal tradition [19]. Given the lake's lifestyle, these individual property rights are used to construct dwellings on stilts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation